Bimbingan Teknis Pengenalan Sistem Informasi UMKM Bantul Pada Kelompok Informasi Masyarakat Kabupaten Bantul - Muhammad Sholeh; Rr. Yuliana Rachmawati; Joko Triyono (LPPM UNINUS, 2019)
The development of information and communication technology has not only changed the way people communicate, but also trading methods. The public has begun to get used to making transactions with information technology. This can be seen with the growth of online stores that offer a variety of products. As SMEs, the change in people's paradigm in transactions must be followed by offers or transactions with information technology. This opportunity must be anticipated by the SMEs. Efforts to support the use of the internet as a promotional medium are to use the MSME information system. This MSME information system is designed to promote MSME principals especially those in Bantul district. In order for the use of this MSME information system to work properly, there needs to be training and assistance in using the system. Mentoring activities have been carried out, especially for community groups incorporated in the Bantul district community information group.